Variation in breeding systems, floral morphology and nectar properties in three co-occurring Erica species with contrasting pollination syndromes - Lombardi, Giorgio Colombo (Rhodes University, Faculty of Science, Botany Department, 2015)
The genus Erica is the most species rich in the Cape Floristic Kingdom, yet there are limited data on the various flower-pollinator interactions and breeding systems for the majority of these species. Until recently research has focussed on predictive floral traits, including flower shape, length of corolla and corolla opening to identify likely pollinators in this genus. Field observations provide an empirical test of such predictions. This study investigated three species of Erica and compared their pollination and breeding systems and floral biology. Research, including field experiments and pollinator observations was undertaken in the Vogelgat Private Nature Reserve, Maanschynkop Nature Reserve and Boskloof farm in the vicinity of Hermanus in the Western Cape Province of South Africa. Field observations were conducted to determine what flower- visitor interactions occurred, while nectar volumes and sugar concentrations were measured to determine the value of the reward to the different visitors. Selective exclusion and breeding system experiments were carried out to determine whether these Erica species were capable of autonomous self-fertilization or whether they are pollinator dependent for breeding success. The unusual morphology of Erica lanuginosa suggested rodent-pollination. Field observations, including photographs of visits to plants in the field, the presence of pollen in scat sample and selective exclusion and breeding system experiments identified rodents, primarily Acomys subspinosus to be the primary pollinator. Long-proboscid flies of the family Nemestrinidae were found, on the basis of field observations to be responsible for pollination of the endemic Erica aristata. This was supported by with nectar volume and sugar concentration samples which are consistent with other long-proboscid fly-pollinated plant species. Selective exclusion and breeding system experiments undertaken confirmed that Erica aristata required a pollinator to set seed. Observations and breeding trials revealed bird-pollination in Erica sessiliflora. Nectar volume and sugar concentrations in Erica sessiliflora were in line with other sunbird-pollinated plant species, providing the necessary rewards for sunbirds visiting this species. Specialised pollination by single pollinators was found in all three species and results from breeding system experiments show that out-crossing is important. Further research into pollinator-flower interactions in the genus Erica is necessary, not least to understand more fully the conservation importance of specific pollinators.
Keywords: Ericas -- South Africa -- Western Cape; Ericas -- Morphology; Ericas -- Reproduction; Ericas -- Pollination; Pollination by animals; Pollination by insects; Nectar